PENGEMBANGAN MODEL PEMBELAJARAN SENI TARI UNTUK PENDIDIKAN GURU SEKOLAH DASAR (ANALISIS TERHADAP KEMAMPUAN PRAKTEK MENARI MAHASISWA PGSD FKIP UNIVERSITAS JAMBI) - Destrinelli Destrinelli (Universitas Batanghari Jambi, 2017)
The need to develop models of learning dance at school Teacher Education students (PGSD) due to the learning model used has not been optimally achieve the expected learning. The results of discussions with the students explained that the measures were implemented learning model can not push the imagination to express motions creatively, students tend to imitate because there is no practical guidelines that help in creative expression. Based on this, is necessary to develop a creative dance learning model to address learning problems PGSD dance students. Referring to the theories put forward, component design study model for PGSD dance which will be developed using: 1) a creative approach, 2) exploratory methods, and 3) the assignment technique, improvisation, and teamwork. This design is called